2005
DOI: 10.1002/ijc.21188
|View full text |Cite
|
Sign up to set email alerts
|

Efficient induction of T‐cell responses to carcinoembryonic antigen by a heterologous prime‐boost regimen using DNA and adenovirus vectors carrying a codon usage optimized cDNA

Abstract: The immunogenic properties of plasmid DNA and recombinant adenovirus (Ad) encoding the carcinoembryonic antigen (CEA) were examined in mice by measuring both the amplitude and type of immune response, and the immunogenicity of codon usage optimized cDNA encoding CEA (CEAopt) was assessed both in C57Bl/6 and CEA transgenic mice. Vectors were injected into quadriceps muscle either alone or in combination, and plasmid DNA was electroporated to enhance gene expression efficiency and immunogenicity. Injection of pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
75
0

Year Published

2006
2006
2009
2009

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 64 publications
(77 citation statements)
references
References 54 publications
2
75
0
Order By: Relevance
“…A number of DNA prime-adenovirus boost regimens were intended to induce cellular immune responses through intramuscular injection [42][43][44][45][46][47][48][49]. Some research groups, however, reported that DNA prime-virus boost regimens stimulated strong humoral immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…A number of DNA prime-adenovirus boost regimens were intended to induce cellular immune responses through intramuscular injection [42][43][44][45][46][47][48][49]. Some research groups, however, reported that DNA prime-virus boost regimens stimulated strong humoral immune responses.…”
Section: Discussionmentioning
confidence: 99%
“…8 Here, we evaluated whether the administration of anti-CD25 mAb could enhance the CEA-specific immune responses.…”
Section: Resultsmentioning
confidence: 99%
“…8 The same CEA codon optimized expression cassette was inserted in an Ad serotype 6 generating Ad6-CEA.…”
Section: Ad Vectorsmentioning
confidence: 99%
“…DNA vaccination in mice was performed via both electroporation according to Rizzuto et al [32] and adenovirus vaccination according to Mennuni et al [17]. Monkey immunization studies were performed at The Biomedical Primate Research Center (BPRC, Rijswijk, The Netherlands) using a group of four rhesus macaques (Macaca mulatta).…”
Section: Vaccination Protocolsmentioning
confidence: 99%
“…It was also shown in rhesus macaques that a mixed vaccination modality, such as DNA followed by adenovirus, later may elicit a more effective immune response including a persistent CD8 response [16]. We have previously assessed the efficacy of a mixed-modality DNA-EP/Adeno against carcinoembryonic antigen (CEA) in hCEA-transgenic mice and showed this vaccine to be able to induce anti-CEA cellmediated immunity as well as partial protection from subsequent tumor challenge [17]. In the present study, we have therefore started to evaluate Ep-CAM as immunogen when delivered by DNA-EP and adenovirus.…”
Section: Introductionmentioning
confidence: 99%